2013
DOI: 10.1186/1751-0147-55-50
|View full text |Cite
|
Sign up to set email alerts
|

Theileria annae in a young Swedish dog

Abstract: A severe regenerative anemia was detected in a 12-week-old mixed breed puppy in Sweden.A small protozoan parasite was observed in erythrocytes on a blood smear. It was initially suspected to be Babesia gibsoni based on its size and because B. gibsoni was previously recorded in Sweden.Surprisingly, specific polymerase chain reaction analysis identified the protozoan as Theileria annae. T. annae is endemic in Northwest Spain, is very uncommonly reported elsewhere and has never been recorded in Scandinavia. T. an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…microti in Hungary. According to Portuguese [ 13 ] and Swedish [ 39 ] researchers, this parasite may be capable of vertical spread and intrauterine transmission to the fetus, as its occurrence has been demonstrated in puppies free of tick infestation. It has also been suggested that, like B. gibsoni [ 40 ], Babesia cf.…”
Section: Discussionmentioning
confidence: 99%
“…microti in Hungary. According to Portuguese [ 13 ] and Swedish [ 39 ] researchers, this parasite may be capable of vertical spread and intrauterine transmission to the fetus, as its occurrence has been demonstrated in puppies free of tick infestation. It has also been suggested that, like B. gibsoni [ 40 ], Babesia cf.…”
Section: Discussionmentioning
confidence: 99%
“…Babesia species (DNA detection by means of conventional PCR technique) were detected in 2.4 % of these samples (Hirsch and Pantchev 2008). However, canine babesiosis is increasingly endemic in both Germany (Barutzki et al 2007) and Switzerland Table 3 Current Babesia / Theileria species in the dog (small forms): at least five genetically different species (according to Zahler et al 2000a,b;Beck et al 2009;Irwin 2009;Birkenheuer 2012;Falkenö et al 2013;Najm et al 2014;Duscher et al 2014;Gallusova et al 2014;Rosa et al 2014;Baneth et al 2015;Farkas et al 2015). (Schaarschmidt et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Among small Babesia species, Babesia microti-like sp. isolates have been identifi ed in Portugal [76], Spain [77], France [78], Croatia [23], Serbia [66] and Sweden [79]. Table 1 presents Babesia species currently identifi ed in dogs with relevant vector tick species and geographical distribution.…”
Section: Taxonomy and Geographic Distributionmentioning
confidence: 99%